ChemInform Abstract: Two Novel Norlignans from Gymnotheca chinensis. Issue 41 (7th October 2014) - Xiao, Shi‐Ji; Lei, Xin‐Xiang; Xia, Bing; Xiao, Hong‐Ping; He, Da‐Hai; Fang, Dong‐Mei; Qi, Hua‐Yi; Chen, Fang; Ding, Li‐Sheng; Zhou, Yan
Abstract isolation and structural elucidation of gymnothedelignans A (I) and B (II)